Validation of primer for promoting maternal self-efficacy in preventing childhood diarrhea - Leidiane Minervina Moraes de Sabino; Ádria Marcela Vieira Ferreira; Elizamar Regina da Rocha Mendes; Emanuella Silva Joventino; Fabiane do Amaral Gubert; Jardeliny Corrrêa da Penha; Kamila Ferreira Lima; Ludmila Alves do Nascimento; Lorena Barbosa Ximenes
ABSTRACT Objective: to validate an educational primer, regarding content and design, for promoting maternal self-efficacy in preventing childhood diarrhea. Method: methodological study composed of 31 mothers of children under five years of age, in which the validation of the primer You can prevent diarrhea in your child! was carried out from the Content Validity Index (CVI), being evaluated as to the domains understanding, attractiveness, self-efficacy, cultural acceptance, and persuasion. Results: the primer was considered relevant and clear, with average concordance of 99.4% and 99.8%, respectively. The overall CVI was of 0.99, evidencing satisfactory level of agreement between the mothers. The assessment of domains generated satisfactory results. Conclusion: the primer was considered valid by the target audience; thus, it can be implemented for promoting maternal confidence to prevent childhood diarrhea.